Psychometric evaluation of the Advanced Systemic Mastocytosis Symptom Assessment Form (AdvSM-SAF). (September 2021) - Taylor, Fiona; Li, Xiaoran; Yip, Christine; Padilla, Brad; Mar, Brenton; Green, Tanya; Oren, Ronny; Boral, Anthony L.; Lin, Hui-Min; Shields, Alan L.; Gotlib, Jason
Highlights: The AdvSM-SAF produced reliable, construct-valid, and sensitive scores when administered in the target patient population. Candidate clinically meaningful between-group differences and within-person change estimates are presented. The AdvSM-SAF is fit for the purpose of measuring treatment benefit in individuals with AdvSM. These are the first psychometric data and score interpretation guidelines presented for the AdvSM-SAF. Abstract: Background: The Advanced Systemic Mastocytosis Symptom Assessment Form (AdvSM-SAF) was developed to evaluate symptoms of advanced systemic mastocytosis (AdvSM). This study aimed to psychometrically evaluate AdvSM-SAF scores and provide score interpretation guidelines. Methods: The 10-item AdvSM-SAF was administered daily (scored as a seven-day average) in EXPLORER, an open-label Phase 1 study in AdvSM. Score distribution, reliability, construct-related validity, sensitivity to change, and interpretation guidelines were evaluated for AdvSM-SAF items, gastrointestinal symptom score (GSS), skin symptom score (SSS), and total symptom score (TSS). Results: Thirty-one patients contributed to the analyses. At Baseline, the GSS, SSS, and TSS had adequate internal consistency (α > 0.7) and test-retest reliability (intraclass correlation coefficients >0.7). AdvSM-SAF scores were moderately to strongly correlated with variables as expected, and distinguished among clinically distinct groups. Observed relationships between change scores in the AdvSM-SAF and other assessments reflect evidence that AdvSM-SAF scores change in concert with other assessments designed to measure similar constructs. The magnitude of AdvSM-SAF weekly TSS mean change scores based on different anchor groupings was as expected (improvement > stable > worsening). Candidate clinically meaningful between-group difference estimates (GSS = 2–4, SSS = 2–3, and TSS = 4–7 points) and within-person change estimates (GSS = 6–9, SSS = 1–4, TSS = 9–14) for AdvSM-SAF weekly scores were generated. Conclusion: The AdvSM-SAF produced reliable, construct-valid, and sensitive scores when administered in the target patient population. These results, along with its strong development history and evidence of content validity, indicate that the AdvSM-SAF is fit for the purpose of measuring treatment benefit in individuals with AdvSM.